A lady has the floor : Belva Lockwood speaks out for women's rights - Hannigan, Kate (Calkins Creek, 2018)
Presents a brief picture book biography of Belva Lockwood, a female lawyer in the United States who lived between 1830 and 1917, one of the earliest feminist activists and women's rights supporters.